Flat plate solar collectors and applications: a review - Muhammad, Bande Yahaya; Adam, Nor Mariah (Universiti Putra Malaysia Press, 2014)
In this study, various methods and applications of flat plate solar collectors are discussed and pictorial representations are presented. Low temperature applications of flat plate collectors are identified in solar cooking, solar water heating, space and air heating, industrial heating plants and in agricultural produce drying processes. Basic equations, as presented by many researchers in the performances of flat plate collectors, are also presented. The review discusses the analysis of losses from flat plate collectors towards obtaining the overall heat loss coefficient which indicate the performance of flat plate collectors.